VEHICLE STARTER SYSTEM FOR SAFETY BASED MICROCONTROLLER USING INTERNET OF THINGS - Rachma Khairunisa; Rahmat Hidayat (TEKNOKOM, 2023)
Technology is currently growing very fast which affects and has a significant purpose in human life. In the current era, the technology of the security system is something that is very necessary. The high crime rate has now reached an alarming stage. Motorcycles currently only use conventional ignition keys to turn them on to improve the vehicle's security system, so a vehicle security system with a microcontroller connected to an Internet of Things-based fingerprint sensor is needed to improve the vehicle's security system. Research shows that a motorcycle security system with a microcontroller is connected to a fingerprint sensor based on the Internet of Things, namely turning on and turning off the vehicle with fingerprints owned or via the internet of things using the telegram application for remote and realtime systems. The way the results of this study work is when the first finger taps on the fingerprint sensor on the registered finger, the motor will turn on, then the second finger taps on the fingerprint sensor, the motor will die, for remote systems, namely using telegram bots, the prefix is to enter chat instructions on the telegram bot if the telegram bot replies to the instruction then the motor will follow according to the instruction on or off and if the instruction is wrong then the telegram bot will tell that the instruction is wrong. The results of this study show that when adding fingerprints it has a delay of 1.74s, removing fingerprints is 0.24s and the IoT system itself is 90% successful.